Leishmania parasitophorous vacuole membranes display phosphoinositides that create conditions for continuous Akt activation and a target for miltefosine in Leishmania infections. (31st July 2018) - Zhang, Naixin; Prasad, Samiksha; Huyghues Despointes, Charles‐Eugene; Young, Jeffrey; Kima, Peter E.
Abstract: Miltefosine is an important drug for the treatment of leishmaniasis; however, its mechanism of action is still poorly understood. In these studies, we tested the hypothesis that like in cancer cells, miltefosine's efficacy in leishmaniasis is due to its inhibition of Akt activation in host cells. We show using pharmacologic agents that block Akt activation by different mechanisms and also using an inducible knockdown approach that miltefosine loses its efficacy when its access to Akt1 is limited. Interestingly, limitation of Akt activation results in clearance of established Leishmania infections. We then show, using fluorophore‐tagged probes that bind to phosphoinositides, that Leishmania parasitophorous vacuole membranes (LPVMs) display the relevant phosphoinositides to which Akt can be recruited and activated continuously. Taken together, we propose that the acquisition of PI(4) P and the display of PI (3, 4)P2 on LPVMs initiate the machinery that supports continuous Akt activation and sensitivity to miltefosine.